Aortopulmonary window. Clinical and surgical assessment of 18 cases - Soares,Andressa Mussi (1999)
OBJECTIVE: Aortopulmonary window (APW) is an uncommon congenital malformation. Its clinical presentation is dependent on the size of the defect and on the associated lesions. We evaluated our experience with this anomaly and compared it with 296 cases reported in the literature. METHODS: Retrospective study of 18 patients diagnosed as having APW (age range from 13 days to 31 years, 13 (72.2%) females), divided into two groups: Group A (GA): 10 patients with isolated APW, and Group B (GB): 8 patients with associated lesions. RESULTS: Heart failure occurred in 14 patients, and cyanosis in 3: 2 from GB (tetralogy of Fallot - TF, and double outlet right ventricle - DORV), and one from GA with pulmonary hypertension. In 5 patients from GA the diagnosis of mitral regurgitation was made based on a systolic murmur and LV hypertrophy on the EKG. In GB, clinical findings were determined by the associated defect. Diagnosis was established by echocardiography in 11 (61.2%) of the patients. In 3 patients, a wrong diagnosis of mitral regurgitation was made, in 1 a patent ductus arteriosus was diagnosed and in 3 others, the diagnosis of APW was masked by other important associated defects (2 cases of DORV and 1 case of TF). The diagnosis was made by catheterization in 3 (16.6%) patients, by surgery in 3 (16.6%) and by necropsy in 1 (5.5%). Corrective surgery was performed in 14 (77.7%) patients, with one immediate death and good long-term follow-up in the remaining patients. CONCLUSION: APW can be confused with other defects. Clinical findings, associated with an adequate echocardiogram can provide the information for the correct diagnosis.